Escalated Care Pathways: A Retrospective Review of Patient-specific Outcomes Following Anterior Cruciate Ligament Injury - Collett, Joel; Reid, Duncan; Harvey, Daniel; Potts, Geoff (New Zealand Society of Physiotherapists Inc, 2025)
Due to increasing rehabilitation costs associated with anterior cruciate ligament (ACL) injury, the Accident Compensation Corporation instigated an innovative pilot scheme, the escalated care pathway (ECP). Introduced in 2019, ECPs were designed to improve patient outcomes through timely assessment and interdisciplinary treatment. The aim of this study was to quantify patient-reported outcome measures, functional measures, and treatment volumes for patients enrolled in one of the ECP pilots following ACL injury. Data including the Knee Osteoarthritis Outcome Score (KOOS), limb symmetry index (LSI), demographic information, number of physiotherapy visits, and overall treatment duration were extracted from the Careway ECP database for patients who completed the programme between 2020 and 2023. Data from 750 patients, surgical (n = 332 (43%); M (SD) age 33.1 (13.1) years) and non-surgical (n = 418, (55.7%); M (SD) age of 35.8 (15.1) years), were analysed. Mean (SD) treatment duration was significantly longer in the surgical (317.2 (141.5) days) vs non-surgical group (285.8 (156.0) days) (p < 0.01). Surgical patients had more physiotherapy visits (25.4 (19.6) vs 13.2 (15.3), p < 0.01). The KOOS improved in both groups; however, the M (SD) change scores between groups (surgical (29.1 (20.0); non-surgical (25.8 (18.4)) were not statistically significant (p = 0.052). Mean (SD) LSI increased from baseline to exit from the programme (surgical 72.3 (26.8) to 100.8 (29.7); non-surgical 77.1 (36.3) to 104.7 (33.3)) (p = 0.055). These findings provide insight for physiotherapists managing ACL injury and demonstrate that surgical and non-surgical patients achieve positive outcomes through the ECP.
Keywords: 1103 Clinical Sciences; 4201 Allied health and rehabilitation science; Anterior Cruciate Ligament; Patient-reported Outcome Measures; Physiotherapy; Surgery